Stereopsis and visual acuity: Bilateral trifocal versus blended extended depth of focus and diffractive bifocal intraocular lenses - Zhu, Meiyi; Fan, Wei; Zhang, Guangbin (Frontiers in Medicine, 2022)
Purpose To compare stereopsis and visual acuity (VA) between bilateral implantation of trifocal intraocular lenses (IOL) and blended implantation of an extended depth of focus (EDOF) IOL with a bifocal IOL. Methods This is a non-randomized, prospective comparative study included 74 eyes of 37 patients who underwent phacoemulsification and bilateral implantation of AT LISA tri 839MP IOL (bilateral group; 21 patients) or blended implantation of Tecnis Symfony ZXR00 and Tecnis ZLB00 IOL (blended group; 16 patients). The primary outcomes were stereoacuity and binocular VA. The secondary outcomes were visual defocus curve, quality of life, and patient satisfaction. Follow-up was performed 3 months after the surgery. Results The mean near stereoacuity was 49.76 ± 22.67 and 120.63 ± 90.94 seconds of arc (arcsec) in the bilateral and blended groups, respectively (P < 0.001). Near stereoacuity was positively correlated with VA difference of two eyes (r = 0.896, P < 0.001). The mean binocular uncorrected visual acuity at 40 cm, 80 cm, 5 m, and corrected distance visual acuity at 5 m of the bilateral and blended groups was not statistically significant different. The bilateral group had better VA at a vergence from −2.5 to −4.0 D. Both groups obtained high quality of life and patient satisfaction scores. Conclusion The bilateral and blended groups achieved good binocular VA, quality of life, and high patient satisfaction. However, the near stereoacuity of the blended group was worse.